Sosialisasi Anti bulliying Sebagai Penguatan Karakter Siswa SDN 21 Lubuk Basung - Ivtahi Sanda; Asrizal Asrizal (CV. ITTC INDONESIA, 2026)
Bullying in schools remains a serious problem that impacts the psychological well-being of victims. This study aims to determine the effectiveness of anti-bullying outreach programs in improving students' understanding and attitudes toward bullying behavior at SD N 21 Lubuk Basung. This research was conducted through the Community Service Program (KKN) using an education-based persuasive approach for grade VB students at SD N 21 Lubuk Basung. The implementation method involved observation, material presentation, and discussion. Data was collected through observation, teacher interviews, and a question-and-answer session. The results showed that initially, students did not understand the meaning of bullying, examples of bullying, and the various types of bullying in the school environment. However, after the outreach program, students' understanding of bullying, examples of bullying, and the various types of bullying increased. Students also demonstrated changes in attitude, marked by the courage to report, remind each other, and reject bullying.